KONSEP MEDAN MAKNA DALAM PEMIKIRAN AHMAD MUKHTAR UMAR DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA ARAB - Raodhatul Fitri; Haniah; Amrah Kasim (JCI Publisher, 2026)
This study aims to examine the concept of semantic fields in the thought of Ahmad Mukhtar Umar and its relevance to Arabic language learning. The research employs a qualitative approach with the library study method, which is based on theoretical analysis of relevant scholarly literature. The data consist of primary and secondary sources. The primary data are obtained from Ahmad Mukhtar Umar’s works discussing ‘ilm al-dalālah (semantics), while the secondary data come from books, journal articles, and websites related to semantics and Arabic language learning. The findings show that Ahmad Mukhtar Umar’s linguistic thought is built upon the integration of classical Arabic linguistic traditions and modern linguistic theories, emphasizing language as a dynamic and contextual system of meaning. The concept of the semantic field is understood as a network of semantic relations among vocabulary items, encompassing synonymy, hyponymy, part–whole relations, antonymy, and incompatibility. The study concludes that applying the concept of semantic fields in Arabic language learning enables thematic and conceptual vocabulary development, thereby supporting more meaningful, communicative, and contextual learning.